Characteristics of GaN/InGaN Double-Heterostructure Photovoltaic Cells - Ming-Hsien Wu; Sheng-Po Chang; Shoou-Jinn Chang; Ray-Hua Horng; Wen-Yih Liao; Ray-Ming Lin (International Journal of Photoenergy)
The p-GaN/i-InxGa1−xN/n-GaN double-heterostructure photovoltaic (PV) cells have been fabricated and the theoretical photovoltaic properties were also calculated in this work. From theoretical simulation, higher efficiency can be obtained in GaN/InGaN double-heterostructure photovoltaic cells with higher In composition in i-InGaN intrinsic layer. GaN/InGaN double-heterostructure photovoltaic cells with In compositions of 10%, 12%, and 14% were fabricated and characterized for demonstrating with the simulated results. The corresponding photoelectrical conversion efficiency of fabricated GaN/InGaN photovoltaic cells with In compositions of 10%, 12%, and 14% is 0.51%, 0.53%, and 0.32% under standard AM 1.5G measurement condition, respectively. GaN/InGaN photovoltaic cells with In composition of 10% showed high open-circuit voltage (Voc) of 2.07 V and fill factor (F.F.) of 80.67%. The decrease of Voc and FF was observed as In composition increasing from 10% to 14%. For comparing with the fabricated GaN/InGaN photovoltaic cells, theoretical conversion efficiency of GaN/InGaN photovoltaic cells with In compositions of 10%, 12%, and 14%, is 1.80%, 2.04%, and 2.27%, respectively. The difference of GaN/InGaN photovoltaic properties between theoretical simulation and experimental measurement could be attributed to the inferior quality of InGaN epilayer and GaN/InGaN interface generated as the increase of In composition.